Evaluation of Preventive Behaviors of Addiction among Students: Application of Health Belief Model - Nasir Muwfaq Younis; Arkan Bahlol. Naji (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Addiction is significant health concern worldwide. Addiction is inveterate trouble which isassociated with significant morbidity and mortality.Objectives: The purpose of this study was to evaluation of preventive behaviors of addiction among studentsin Mosul City during apply of Health Belief ModelMaterials and Method: This study is based on descriptive design and includes randomly selected studentsin Mosul University included (Political Science, Engineering, Sciences and Nursing Colleges). The samplesize was (80) students. Data were gathered in 1st of October / 2019 till 12 of May / 2020 using a questionnairemethod. The instrument consist of two parts; part I, involved, to describe the student’s socio-demographiccharacteristic such as (age, gender, grade, college ,socioeconomic status) the part II, involved the using scaleto measure students’ beliefs towards of addiction.Results: demonstrated that the results of study the overall mean age for the participants was 23.53 (SD =2.06). Concerning body mass index (BMI) most of participants were normal body weight. The overall meanBMI for participants was 21.23 (SD = 2.53).Conclusion: These researchers found that the Health Belief Model concepts toward addiction were the nosignificant improvement.